Facts About Wildlife Diseases: Eastern Equine Encephalitis: WEC-408/UW453, 4/2019 - Wisely, Samantha M; Hood, Karen (EDIS, 2019)
The Eastern equine encephalitis virus (EEEV) causes Eastern equine encephalitis (EEE) disease in birds, humans, horses, and other animals in the eastern United States, including Florida, which is especially receptive to the virus because of its freshwater hardwood swamps and wetlands, which provide good niches for the mosquito vectors of the disease. This 5-page fact sheet written by Samantha Wisely and Karen Hood and published by the UF/IFAS Department of Wildlife Ecology and Conservation describes the disease and includes strategies for limiting its spread. http://edis.ifas.ufl.edu/uw453